CHOICE OF REVASCULARIZATION TECHNIQUE IN PATIENTS WITH ISCHEMIC DIABETIC FOOT - D. Shapovalov (State Institution of Science «Research and Practical Center of Preventive and Clinical Medicine» State Administrative Department, 2021)
Background